Estimating accidental pollutant releases in the built environment from turbulent concentration signals. (January 2017) - Ben Salem, N.; Salizzoni, P.; Soulhac, L.
Abstract: We present an inverse atmospheric model to estimate the mass flow rate of an impulsive source of pollutant, whose position is known, from concentration signals registered at receptors placed downwind of the source. The originality of this study is twofold. Firstly, the inversion is performed using high-frequency fluctuating, i.e. turbulent, concentration signals. Secondly, the inverse algorithm is applied to a dispersion process within a dense urban canopy, at the district scale, and a street network model, SIRANERISK, is adopted. The model, which is tested against wind tunnel experiments, simulates the dispersion of short-duration releases of pollutant in different typologies of idealised urban geometries. Results allow us to discuss the reliability of the inverse model as an operational tool for crisis management and the risk assessments related to the accidental release of toxic and flammable substances. Highlights: We present an inverse model for accidental pollutant releases in a built environment. The model are tested against wind tunnel experiments. Results support the use of the model as operational tool for risk assessment.